2020
DOI: 10.1002/pros.23971
|View full text |Cite
|
Sign up to set email alerts
|

Screening for chronic prostatitis pathogens using high‐throughput next‐generation sequencing

Abstract: Background The pathogens responsible for chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS; NIH category III) are not currently known. the present study utilized high‐throughput next‐generation sequencing to screen for potential pathogens associated with NIH category III CP (CP III). Methods This study included 33 patients with CP III and 30 healthy men, from which one sample each of urethral secretions and expressed prostatic secretion (EPS) was collected. High‐throughput next‐generation sequencing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The urinary tract was previously believed to be sterile; however, recent studies using genetic methods have demonstrated that the urinary tract contains a microbiota 19 . The urinary tract microbiota is suggested to be involved in various urological diseases, such as urge urinary incontinence in women, 20 LUTS in men, 21 BPH, 22 chronic prostatitis, 23,24 and prostate cancer 22,25,26 . Because the urinary tract microbiota is related to the gut microbiota, 27 the gut microbiota may influence prostate enlargement via the urinary tract microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The urinary tract was previously believed to be sterile; however, recent studies using genetic methods have demonstrated that the urinary tract contains a microbiota 19 . The urinary tract microbiota is suggested to be involved in various urological diseases, such as urge urinary incontinence in women, 20 LUTS in men, 21 BPH, 22 chronic prostatitis, 23,24 and prostate cancer 22,25,26 . Because the urinary tract microbiota is related to the gut microbiota, 27 the gut microbiota may influence prostate enlargement via the urinary tract microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Three The hypervariable region targeted by the primer was V4 solely in 17 studies [20,22,30,[32][33][34][35]38,[40][41][42][43]45,48,49,55,56]; V3 in one study [28]; V6 in two studies [31,44]; V9 in one study [27]; V3-V4 in four studies [21,37,50,54]; V1-V3 in one study [19]; V1-V2 in one study [29]; V3-V5 in one study [39]; V4-V6 in one study [36]. One study used primers targeting V2, 4, 8 and V3, 6, 7, 9 regions [24], and one study targeted V1-3 and V4-6 regions [26].…”
Section: Mitigating the Impact Of Contamination During Dna Extraction Sequencing And Data Analysismentioning
confidence: 99%
“…In eight studies (21%), the level of contamination comparing samples to control was discussed in the article [20,28,29,[34][35][36]44,55]. In the other articles, this issue was not discussed.…”
Section: Mitigating the Impact Of Contamination During Dna Extraction Sequencing And Data Analysismentioning
confidence: 99%
See 2 more Smart Citations